Characteristics of carcass, meat and subcutaneous fat of Mangalica pigs reared outdoors - Nchama, Castro Ndong Ncogo; Saccà, Elena; Sepulcri, Angela; Foletto, Vinicius; Brunner, Ilario; Corazzin, Mirco; Piasentier, Edi (Agriculture and Natural Resources, 2023)
Importance of the work: Mangalica pig meat has a reputation for superior quality. Little information is available on this breed reared for heavy pig production. Objectives: To evaluate the effects of sex on the carcass, loin and lard characteristics (inner and outer layers) of Blonde Mangalica pigs. Materials & Methods: In total, 15 Blonde Mangalica pigs were considered (10 castrated males and 5 females) that were reared together outdoors. The pigs had ad libitum access to the same diet and were slaughtered at age 22.9 mth, with an average carcass weight of 141.4 kg. Results: Sex did not affect the carcass, meat or lard characteristics. In general, the Mangalica pigs had an average fat thickness of 70 mm and a loin cholesterol content of 0.674 mg/g. The loin had 39.0%, 52.5% and 8.5% saturated (SFA), monounsaturated fatty acids and polyunsaturated fatty acids (PUFA), respectively. Significant differences were found in the characteristics of the two lard layers. In particular, the inner layer was brighter and had a higher dry matter content than the outer layer. Regarding the fatty acids content, the inner layer had a lower PUFA but higher SFA content. Main finding: Sex did not influence the carcass, meat or lard characteristics of the Mangalica pigs. The results improved the characterization and filled knowledge gaps regarding meat and lard quality parameters of heavy Mangalica pigs reared outdoors.